X-class Flare on 2023 December 31 Observed by the Solar Ultraviolet Imaging Telescope on Board Aditya-L1 - Soumya Roy; Durgesh Tripathi; Vishal Upendran; Sreejith Padinhatteeri; A. N. Ramaprakash; Nived V. N.; K. Sankarasubramanian; Sami K. Solanki; Janmejoy Sarkar; Rahul Gopalakrishnan; Rushikesh Deogaonkar; Dibyendu Nandy; et al. (The Astrophysical Journal Letters)
We present the multiwavelength study of the ejection of a plasma blob from the limb flare SOL2023-12-31T21:36:00 from NOAA 13536 observed by the Solar Ultraviolet Imaging Telescope (SUIT) on board Aditya-L1. We use SUIT observations along with those from the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory and Spectrometer/Telescope for Imaging X-rays (STIX) on board Solar Orbiter to infer the kinematics and thermal nature of the ejected blob and its connection to the associated flare. The observations show that the flare was comprised of two eruptions. The blob was ejected during the first eruption and later accelerated to velocities over 1500 km s ^−1 measured at a maximum projected height of ∼178 Mm from the Sun’s surface. The acceleration of the ejected plasma blob is cotemporal with the bursty appearance of the hard X-ray light curve recorded by STIX. Radio spectrogram observations from STEREO-A/WAVES and RSTN reveal type III bursts at the same time, indicative of magnetic reconnection. DEM analysis using AIA observations suggests the plasma blob is comprised of cooler and denser plasma in comparison to the ambient corona. To the best of our knowledge, this is the first observation of such a plasma blob in the near-ultraviolet providing crucial measurements for eruption thermodynamics.